1983
DOI: 10.1104/pp.72.2.557
|View full text |Cite
|
Sign up to set email alerts
|

Host-Pathogen Interactions

Abstract: The biochemical basis for the ability of the pterocarpan phytoalexin glycinol (3,6a,9-trihydroxypterocarpan) to inhibit the growth of bacteria was examined. Glycinol These data imply that the antimicrobial activity of glycinol, glyceollin, and coumestrol are due to a general interaction with the bacterial membrane. Capsidiol (50 micrograms per milliliter) inhibits -lactate-dependent transport of I14CIglycine but not vectorial phosphorylation-mediated transport of 114CIa-methyl glucoside. Thus, capsidiors mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Therefore, it appears that the inhibition of specific target enzymes might be the primary mode of the antibiotic effect of glyceollin. However, as shown in the present study, glyceollin-resistant B. japonicum cells tolerate concentrations of glyceollin up to 440 ,M. Such high concentrations have been reported to disturb membrane integrity (44).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, it appears that the inhibition of specific target enzymes might be the primary mode of the antibiotic effect of glyceollin. However, as shown in the present study, glyceollin-resistant B. japonicum cells tolerate concentrations of glyceollin up to 440 ,M. Such high concentrations have been reported to disturb membrane integrity (44).…”
Section: Discussionsupporting
confidence: 56%
“…While some results suggest a nonspecific mode of action involving disruption of membrane integrity (44), other data support the hypothesis that glyceollin works via specific sensitive target enzymes such as ATPase (12) or NADH-ubiquinone-oxidoreductase (2). From unpublished data, we know that the NADH-ubiquinone-oxidoreductase of B. japonicum 110spc4 is highly sensitive to glyceollin, being strongly affected at concentrations as low as 2 ,uM.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The loss of virulence of some mutants could result either from the disappearance of a structure (LPS) protecting the bacterium from potential defense mechanism or allowing the initial stage of the disease, or from the appearance of a structure (LPS) able to elicit plant defense response. In the first context, some rough mutants, like the two avirulent mutants, might be more susceptible to antimicrobial agents (20) such as phytoalexins (25,35) or might be enhanced in the release of some signal able to induce such host defetse mechanisms (7). Alternatively, exposure of a specific portion of the LPS might allow it to serve as bacterial receptor (or signal) for some plant factor(s) (as lectins for instance), resulting then in drastic bacterial agglutination (30).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that Glys potentially exhibit their antibacterial effects by inhibiting cellular processes and altering the structural integrity of bacterial membranes, thereby impeding bacterial growth (Weinstein and Albersheim 1983).…”
Section: Bactericidal Towards Bacillus Subtilis Bacillus Licheniformmentioning
confidence: 99%